Parents’ attitudes and views regarding antibiotics in the management of respiratory tract infections in children: a qualitative study of the influence of an information booklet - Dekker, Anne RJ (BJGP Open, 2018)
BACKGROUND: Respiratory tract infection (RTI) is the most common reason to consult a GP during childhood, and often results in unnecessary prescribing of antibiotics. Using an information booklet during the consultation has been shown to be a promising tool to reduce antibiotic prescribing. The influence of such information on parents’ views, knowledge, and expectations has not been investigated yet. AIM: To explore the reported attitude and knowledge of parents towards antibiotics and management of childhood RTI, as well as the added influence of an information booklet, as perceived by parents. DESIGN & SETTING: Qualitative interviews were conducted with Dutch parents who consulted the GP with their child for RTI symptoms and received an information booklet. METHOD: Semi-structured interviews were audio-recorded, transcribed, coded, and analysed using framework analysis by open-axial coding and describing themes. RESULTS: Eighteen parents were interviewed. Four themes were identified: prior reticence towards antibiotics; expectations of the consultation and trust in the GPs’ treatment decision; confirmation and reassurance by the booklet; self-management and future consultation intentions. Dutch parents felt reassured and more confident about their pre-existing reticent attitude towards antibiotic treatment; therefore, they thought their opinion and attitude had not really been changed by the booklet. CONCLUSION: In a low-prescribing country like the Netherlands, information should focus on enhancing self-efficacy and providing concrete safety-netting advice. For other countries with less reticence towards antibiotics, it is recommended that the knowledge, attitude, and perceptions of the population is studied, in order to be able to tailor interventions.